From Markets to Mobile Phones: The Evolution of Buying and Selling in the All-Digital Era - Desi Endang Maisuri; Faridatul Jannah (Interkoneksi: Journal of Computer Science and Digital Business, 2026)
This study examines the transformation of buying and selling systems from conventional models to the digital systems that have become increasingly dominant in the modern era. The research aims to understand how the development of digital technology influences transaction patterns, consumer behavior, and the strategies employed by business players to adapt to these changes. A qualitative method utilizing a library research approach was employed, involving the collection and analysis of relevant written sources such as books, scholarly journals, research reports, and online articles. The findings indicate that digitalization has brought about a significant shift in trading activities. Transactions that were once conducted face-to-face have transitioned to digital platforms, offering convenience, speed, and broader market reach. While creating opportunities for businesses—particularly MSMEs—this shift also presents new challenges, such as heightened competition, data security risks, and the need for digital literacy among the public. Overall, the evolution of buying and selling in the digital era demonstrates that success in navigating these changes depends heavily on adaptability, the utilization of technology, and an understanding of ethics in online transactions.